The Merck index : an encyclopedia of chemicals, drugs, and biologicals - O'Neil, Maryadele J., ....- (Whitehouse Station (N.J.) : Merck, 2001)
The Merck Index, 13th Edition is a one-volume encyclopedia of chemicals, drugs, and biologicals that contains more than 10,000 monographs. Each monograph in this authoritative reference source is a concise description of a single substance or a small group of closely related compounds.
Ill. on lining papers.
Includes indexes.
Keywords: Biomolecules -- Dictionaries; Chemicals -- Dictionaries; Chemie -- Encyclopedieën; Drugs -- Dictionaries; Geneesmiddelen; Organische verbindingen